Rum fights to avoid the knock-out punch. - HORNER, Simon (1997)
Looks at the impact of the US-EC Accord on Rum which was agreed to in principle at the WTO Conference in Singapore. In its original form, the accord allowed the Europeans and Americans to remove all levies on imported rum, thereby exposing the Caribbean industry to the full rigours of international competition. Notes that after much lobbying, rum imports in the USA and the EU will now be subject to a special system which meets some of the concerns of the Caribbean industry.